2023
DOI: 10.1177/20414196221149752
|View full text |Cite
|
Sign up to set email alerts
|

Far-field positive phase blast parameter characterisation of RDX and PETN based explosives

Abstract: A significant amount of scientific effort has been dedicated to measuring and understanding the effects of explosions, leading to the development of semi-empirical methods for rapid prediction of blast load parameters. The most well-known of these, termed the Kingery and Bulmash method, makes use of polylogarithmic curves derived from a compilation of medium to large scale experimental tests performed over many decades. However, there is still no general consensus on the accuracy and validity of this approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Farrimond et al . [17] present a detailed argument that, given careful control over the test conditions, the expected variability in recorded unconfined blast wave parameters should typically be no more than a few per cent of the mean in far-field scaled regimes ( true0 > 3 m/kg true0 1 / 3 ). A key aim of this study was to assess whether this level of consistency could be observed in the far more complex case of a confined detonation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Farrimond et al . [17] present a detailed argument that, given careful control over the test conditions, the expected variability in recorded unconfined blast wave parameters should typically be no more than a few per cent of the mean in far-field scaled regimes ( true0 > 3 m/kg true0 1 / 3 ). A key aim of this study was to assess whether this level of consistency could be observed in the far more complex case of a confined detonation.…”
Section: Resultsmentioning
confidence: 99%
“…The previous work published by Farrimond et al . [17] characterized PE4, PE8 and PE10 in far-field area-style trials, within which very similar explosive yields were recorded. Presented in this article is an investigation into whether the same explosive compositions behave in a similar manner within a confined scenario.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the improved performance of the new MaCE pressure bars, this section provides a comparison between CoBL and MaCE facility pressure measurements in the extreme near field. These tests were performed at m/kg , near the limit of the existing CoBL pressure bars, using the plastic explosive PE10 (86% PETN, 14% plasticiser; TNT [ 30 ]). Separate tests were performed in CoBL and MaCE using the same charge arrangement: a 113 g sphere of PE10 was positioned at a stand-off distance of 95 mm (charge centre to target plate surface) by suspending it between two vertical supports in a strip of lightweight glass fibre netting.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…Scaled distance, Z, can be calculated via Equation (1). These scaling laws allow direct comparisons between explosive events at any reasonable scale, provided the differences in the explosive compounds are accounted for (e.g., shape effects [17][18][19][20], secondary combustion [21], heat of detonation and/or reaction rates [22][23][24][25], etc.). However, some have previously suggested a practical limit to the minimum reasonable scale for gathering experimental data [26].…”
Section: Current Knowledge 21 Basic Theorymentioning
confidence: 99%